2021
DOI: 10.3389/fimmu.2021.774273
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Preserves Oral Cavity Health by Mitigating Inflammation and Microbial Dysbiosis

Abstract: Failure to attenuate inflammation coupled with consequent microbiota changes drives the development of bone-destructive periodontitis. Quercetin, a plant-derived polyphenolic flavonoid, has been linked with health benefits in both humans and animals. Using a systematic approach, we investigated the effect of orally delivered Quercetin on host inflammatory response, oral microbial composition and periodontal disease phenotype. In vivo, quercetin supplementation diminished gingival cytokine expression, inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 125 publications
(156 reference statements)
0
27
0
1
Order By: Relevance
“…Moreover, previous reports have found that quercetin can inhibit the release of inflammatory cytokines in human gingival fibroblasts (HGFs) stimulated by Porphyromonas gingivalis lipopolysaccharide in vitro and alleviate alveolar bone resorption in in vivo animal models [ 14 , 15 , 16 , 17 ]. Although several studies identify QUE as a promising phytochemical to sustain periodontal tissue health, the poor bioavailability, high metabolic rate, and rapid clearance from body of QUE limit its clinical application [ 18 ]. Therefore, the development of local delivery platforms that would overcome the biopharmaceutical obstacles and avoid systemic clearance of QUE, thereby increasing its therapeutic and prophylactic potential, is still a technological challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous reports have found that quercetin can inhibit the release of inflammatory cytokines in human gingival fibroblasts (HGFs) stimulated by Porphyromonas gingivalis lipopolysaccharide in vitro and alleviate alveolar bone resorption in in vivo animal models [ 14 , 15 , 16 , 17 ]. Although several studies identify QUE as a promising phytochemical to sustain periodontal tissue health, the poor bioavailability, high metabolic rate, and rapid clearance from body of QUE limit its clinical application [ 18 ]. Therefore, the development of local delivery platforms that would overcome the biopharmaceutical obstacles and avoid systemic clearance of QUE, thereby increasing its therapeutic and prophylactic potential, is still a technological challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[8] suggest that a diet supplemented with the citrus flavonoids eriocitrin or eriodictyol may help prevent periodontitis, providing a potential method of enhancing local immunity and host defence. Mooney EC et al [9] showed that orally-administered quercetin helps maintain the health of periodontal tissues by alleviating inflammation, and promotes the development of symbiotic bacterial flora. This may prove to be an efficient treatment option due to its high tolerability and safety profile, as an inexpensive and feasible long-term supplement in patient populations with chronic diseases, including those prone to periodontal disease.…”
Section: Review and Discussionmentioning
confidence: 99%
“…According to previous studies, quercetin has been shown to possess strong antiinflammatory capacity (Mooney et al, 2021;Riemschneider et al, 2021). It exerts antiinflammatory effects on several cell types in both animals and humans (Chen, Zhang, et al, 2020;Fan et al, 2019).…”
Section: Antiinflammatory Role Of Quercetinmentioning
confidence: 99%